An approach of security testing for third‐party component based on state mutation. Issue 15 (23rd January 2015) - Chen, Jinfu; Chen, Jiamei; Huang, Rubing; Guo, Yuchi; Zhan, Yongzhao
ABSTRACT: It is essential to study an effective approach of security testing for third‐party component. In this paper, to effectively trigger implicit vulnerabilities of third‐party components, an approach of security testing for third‐party component is proposed based on state mutation. To start with, executable method sequences of components are transformed into extended finite state machine. Then, according to characteristics of condition conflict and behavior conflict, two test case generation algorithms are addressed, that is, Operations Conflict Sequences Generation Algorithm and Conditions Conflict Sequences Generation Algorithm, which are designed to generate inaccessible sequences of behavior and condition conflicts. These conflict sequences are run. Furthermore, the security detecting algorithms are addressed to detect implicit vulnerabilities of third‐party components, and then, testing report of component security is obtained. In the end, some experiments are conducted on the basis of the proposed approach, and the experimental results show that the proposed approach can effectively detect security exceptions of third‐party components. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, two test cases generation algorithms are proposed on the basis of state mutation and extended finite state machine, that is, Operations Conflict Sequences Generation Algorithm and Conditions Conflict Sequences Generation Algorithm, which are designed to generate inaccessible sequences of behavior and condition conflicts. These conflict sequences are run. Furthermore, the security detecting algorithms are addressed to detect implicit vulnerabilities of third‐party components, and then, testing report of component security is obtained.